Aggressive operative treatment of isolated blunt traumatic brain injury in the elderly is associated with favourable outcome. Issue 9 (September 2015) - Wutzler, Sebastian; Lefering, Rolf; Wafaisade, Arasch; Maegele, Marc; Lustenberger, Thomas; Walcher, Felix; Marzi, Ingo; Laurer, Helmut; the TraumaRegister DGU, Committee on Emergency Medicine, Intensive Care; Trauma Management of the German Trauma Society (Sektion NIS)
Abstract Outcome after traumatic brain injury (TBI) in the elderly has not been fully elucidated. The present retrospective observational study investigates the age-dependent outcome of patients suffering from severe isolated TBI with regard to operative and non-operative treatment. Data were prospectively collected in the TraumaRegister DGU®. Anonymous datasets of 8629 patients with isolated severe blunt TBI (AISHead ≥ 3, AISBody ≤ 1) documented from 2002 to 2011 were analysed. Patients were grouped according to age: 1–17, 18–59, 60–69, 70–79 and ≥80 years. Cranial fractures (44.8%) and subdural haematomas (42.6%) were the most common TBIs. Independent from the type of TBI the group of patients with operative treatment declined with rising age. Subgroup analysis of patients with critical TBI (AISHead = 5) revealed standardised mortality ratios (SMRs) of 0.81 (95% CI 0.75–0.87) in case of operative treatment (n = 1201) and 1.13 (95% CI 1.09–1.18) in case of non-operative treatment (n = 1096). All age groups ≥60 years showed significantly reduced SMRs in case of operative treatment. Across all age groups the group of patients with low/moderate disability according to the GOS (4 or 5 points) was higher in case of operative treatment. Results of this retrospective observational study have to be interpreted cautiously. However, good outcome after TBI with severe space-occupying haemorrhage is more frequent in patients with operative treatment across all age groups. Age alone should not be the reason for limited care or denial of operative intervention.